The inspection panel : (World Bank, 2008)
The Inspection Panel is dedicated to providing an effective forum to which people affected by a World Bank-financed project or program can complain if they have suffered or may suffer harm because the World Bank has not followed its policies and procedures. This annual report provides information on the Panel's activities during the period July 1, 2007 through June 30, 2008.